Mechanical Characteristics of Stearic Acid Addition in Polylactic Acid (PLA) and Cassava Starch Bioplastic Blends - Yusuf, Muhammad; Fatah, Ghaibi Alimul; Wibowo, Robertoes Koekoeh Koentjoro; Pradiza, Revvan Rifada; Ilyas, Rushdan Ahmad; Asrofi, Mochamad (Green Engineering Society, 2025)
This study aims to determine the effect of adding stearic acid (SA) to a bioplastic mixture of cassava starch (CS) and polylactic acid (PLA). The bioplastic was produced using a solvent casting method. The addition of SA can affect the mechanical properties of the film. The maximum tensile strength of the film increased from 5.12 MPa (without SA) to 7.61 MPa (5% SA). The same trend also applies to the Young's modulus and elongation at break, which increased from 25.45 MPa and 20.17% to 35.02 MPa and 21.64% after the addition of 5% SA. This improvement in mechanical properties is supported by the compatibility of PLA and CS due to the optimal presence of SA. These findings prove that SA is an effective compatibilizer in improving the mechanical properties of PLA and CS-based bioplastics. The resulting film products have the potential to be used as environmentally friendly packaging materials that are competitive with synthetic materials such as Low-Density Polyethylene (LDPE) and Ethylene Vinyl Acetate (EVA).